PENGARUH FAKTOR EKONOMI DAN SOSIAL TERHADAP FERTILITAS PEKERJA PEREMPUAN DI KECAMATAN SIAK HULU KABUPATEN KAMPAR - Lapeti Sari, Riri Dwi Wahyuni , Yusni Mulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of family income, latest education, age at first marriage, frequency of marriage, and type of work on the fertility of female workers in Siak Hulu District, Kampar Regency. The method of determining the type of sample in the study is to use the Random Sampling method with a sample size of 124 female workers who are married / have ever been married. The type of data analysis method in this study is multiple linear regression, statistical testing f test, t test, R2 determinant coefficient and classical assumption testing normality test, heteroscedasticity test and multicollinearity test. The tool used in this research is the EViews 10 program. The results of this study explain that there is a significant influence between family income (X1), last education (X2), age at first marriage (X3), frequency of marriage (D), and type of work (D) simultaneously on fertility (Y) of female workers, partially family income, last education, age at first marriage, and type of work have a significant negative effect on fertility of female workers, while frequency of marriage has a significant positive effect on fertility of female workers. The dominant factor influencing fertility of female workers is age at first marriage. The effect caused by the independent variables on the dependent variable (R2) is 70%, while the remaining 30% can be influenced by other factors outside the variables in this study.Keyword : Social, Economic, Demographic, Fertility, Female Workers